Metaphysical doctrines of the Anlo of Ghana and Process philosophy - (:unkn) unknown (My University, 2022)
The concepts of mutuality and interdependence, process, and God occupy important roles in the doctrines of process thought. Hitherto, very little attention was given to evidence of process metaphysics originating from traditional African religion. Based on this, my paper attempts to reconcile these seemingly different spheres of metaphysics that have been sparingly discussed. I offer, firstly, an account of Alfred North Whitehead's process metaphysics on the tripartite concepts earlier specified. Secondly, I argue that non-conventional sources of African philosophy indeed offer conceptual resources that could nourish our understanding of their philosophies and their place in the metaphysical debate. I further explicate how, through comparative philosophy, African ideas can assume a novel dimension understood as the discussion of doctrines of Africa, by Africans and/or about Africa. Thirdly, I discuss these three key areas in Anlo traditional precolonial thought, and I illustrate their affinity towards process metaphysics through language, religious practices and historical accounts. Finally, I conclude that although Whiteheadian process philosophy overlaps in prominent areas with Anlo belief systems, questions of the limits of the causal nature of God as well as the potency of atonements distinguish the Anlo conception of God from that of process philosophy.
Keywords: African Research